Teuku Umar Leadership as Reflection of Islamic Leadership - Zainal Putra; Jasman J. Ma’ruf (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2022)
This article aims to explore the relevance of Teuku Umar’s leadership with the concept of Islamic leadership played by the Prophet Muhammad (saw) as the great leader of Muslims. The article was written by studying in-depth the history of Teuku Umar from various existing literature and synthesizing the values of leadership based on the history of his struggle. Then observe its relevance to Islamic leadership based on the sources of the Holy Qur’an, Sunnah, and the life history of the Prophet Muhammad (saw). The results conclude that the Teuku Umar leadership concept that has been proposed is very relevant to Islamic teachings. This was greatly influenced by the figure of Teuku Umar, who lived under the Islamic Kingdom of Aceh Darussalam from childhood until the end of his life. Teuku Umar was a Muslim like the majority of the people of Aceh at that time.